THE EFFECT OF ACCOUNTABILITY AND TRANSPARENCY ON THE EFFECTIVENESS OF PAREPARE SHARIA STATE SAVINGS BANK - Humeirah, Zahra; Purnamasari, Rini; Nur, Sri Wahyuni (Institut Agama Islam Negeri Parepare, 2025)
Bank Tabungan Negara Syariah Parepare faces the problem of lack of transparency and accountability. Customers complain about the lack of disclosure of information related to products, services, and financial conditions. In addition, unclear reports indicate the weak accountability of banks in fund management in accordance with sharia principles. The problems raised in this study are based on the lack of transparency and accountability in the management of funds and information to customers, which has an impact on declining trust and service effectiveness. This study aims to determine the Influence of Accountability and Transparency on the Effectiveness of the Parepare Sharia State Savings Bank (BTN). This study uses a field research approach with a quantitative method. The research data was obtained from the results of questionnaires and observations. The research sample was 100 customers of the Parepare Syariah State Savings Bank using the slovin technique. The data analysis technique used is quantitative analysis using SPSS. The results of the study showed that the multiple linear regression test was known to have a sig value for the Accountability variable of 0.009<0.05, and the Transparency variable was 0.024<0.05, meaning that Accountability and Transparency had an effect on the effectiveness of the Parepare Sharia State Savings Bank. So it can be concluded that H1 and H2 are accepted, the results of the analysis show that the two independent variables together have a significant effect on effectiveness with a calculated F value of 10.371 and a significance value of 0.000<0.05, then it can be concluded that H3 is accepted. The test of the determination coefficient (R2) X1,X2 and Y was 18.1% while the remaining 81.9% was explained by other variables outside this model.